Propuesta para la creación de una micro empresa de Diseño Gráfico Publicitario en el Cantón Otavalo. - Maldonado Toapanta, Mauricio Israel (2015)
This document presents an investigation in order to determine feasible means for the implementation of the subject, taking into account the requirements for initialization and proposal development. This analysis consists of using an applied research methods and techniques to get the desired results research. First, a study of the shortcomings that exist in the graphic medium is made, finding shortcomings in meeting the needs of the demand. Chapter I. - aims to fulfill the needs were established by the demand is still creating a micro business Graphic Design Advertising in Canton Otavalo, identifying characteristics required to meet the demands of the customers, the first thing we did was an analysis and data collection in order to obtain theoretical bases and livelihood as well as to the justification for it, implementing meanings as symbol logo, graphic design, advertising, color, etc.. In Chapter II diagnosis -. A research study was made to find out what the requirements are and in turn demand to know what kind of advertising exists in the local environment. A study on the financial means for initializing the project was conducted. An operational proposal analyzing each strategic point for initialization of the project, the image that will get the new advertising graphic design studio, setting the necessary parameters of knowledge about this topic was created was made in Chapter III.